Use of probe-based confocal laser endomicroscopy (pCLE) in gastrointestinal applications. A consensus report based on clinical evidence. Issue 3 (June 2015) - Wang, Kenneth K; Carr-Locke, David L; Singh, Satish K; Neumann, Helmut; Bertani, Helga; Galmiche, Jean-Paul; Arsenescu, Razvan I; Caillol, Fabrice; Chang, Kenneth J; Chaussade, Stanislas; Coron, Emmanuel; Costamagna, Guido; et al.
Background: Probe-based confocal laser endomicroscopy (pCLE) provides microscopic imaging during an endoscopic procedure. Its introduction as a standard modality in gastroenterology has brought significant progress in management strategies, affecting many aspects of clinical care and requiring standardisation of practice and training. Objective: This study aimed to provide guidance on the standardisation of its practice and training in Barrett's oesophagus, biliary strictures, colorectal lesions and inflammatory bowel diseases. Methods: Initial statements were developed by five group leaders, based on the available clinical evidence. These statements were then voted and edited by the 26 participants, using a modified Delphi approach. After two rounds of votes, statements were validated if the threshold of agreement was higher than 75%. Results: Twenty-six experts participated and, among a total of 77 statements, 61 were adopted (79%) and 16 were rejected (21%). The adoption of each statement was justified by the grade of evidence. Conclusion: pCLE should be used to enhance the diagnostic arsenal in the evaluation of these indications, by providing microscopic information which improves the diagnostic performance of the physician. In order actually to implement this technology in the clinical routine, and to ensure good practice, standardised initial and continuing institutional training programmes should be established.